Angka Kuman Susu Formula Pasca Seduh pada Penyimpanan Suhu Lemari Pendingin dengan Variasi Lama Penyimpanan - Mamay Mamay; Iin Patimah; Ernawati Ernawati; Aldi Renaldi Septian (Jurnal Kesehatan, 2023)
One of the factors that influence the incidence of diarrhea in infants is formula feeding. Statistical results show that there is a relationship between formula feeding and the incidence of diarrhea in infants aged 0-6 months. Formula milk should be consumed immediately after brewing. Storage in the refrigerator can be done if formula milk is not consumed immediately to reduce the risk of microbial growth, one of which is bacteria. This study aims to calculate the number of germs or bacteria in post brewed formula milk in the refrigerator with several storage times, namely 0, 12, 24 and 36 hours. This research is an experimental study. The shelf life of 0 and 12 hours, the total germ count, which is 1.103, is still below the threshold for microbial counts and able for consumption. As for the 24-hour shelf life and 36-hour shelf life, the total has exceeded the microbial count threshold > 1.104 and is not good for consumption. Total microbes increased with the length of storage period at refrigerator temperature. It is expected not to consume post-boiled milk that is stored in the refrigerator for more than 12 hours.